Investigation into improved characteristics of nanocomposites of kenaf and basalt fibers strengthened with titanium oxide nanoparticles - T. Sathish; Jayant Giri; Ibrahim Albaijan (AIP Advances, 2024)
This study explores the thermal and mechanical properties of a composite material formed by blending kenaf and basalt fibers with titanium oxide nanoparticles. To assess its performance under various conditions, we conducted thermogravimetric analysis (TGA) and hardness, sorptivity, and water absorption tests. During experimentation, composite samples were created using kenaf and basalt fibers as the reinforcing matrix and TiO2 nanoparticles as the modifier. Initial findings suggest that the addition of TiO2 nanoparticles enhances the mechanical properties and water resistance of the kenaf and basalt fiber composite. Samples reinforced with TiO2 demonstrated superior hardness and lower water absorption, i.e., KBT2 exhibited a hardness of 92 Hv and a water absorption rate of 6.4%. The value of 0.1% for KBT2 from the sorptivity investigation was promising, indicating its potential applicability in moisture-sensitive environments. In addition, TGA results show that KBT2 exhibited 0%, 2.1%, 4.7%, and 8.3% weight loss, showing improved thermal stability and high resilience to higher temperatures. In conclusion, the development of a novel material combining kenaf and basalt fibers reinforced with TiO2 nanoparticles presents a promising eco-friendly, durable, and lightweight option for engineering applications. Realizing the full potential of this composite material necessitates further characterization and optimization research.